Społeczne konteksty komunikacji zapośredniczonej przez media - Maj, Beata (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
The multimedia became the area, where various important needs are fulfilled. It is confirmed by my research carried out in the year 2017 on a group of students of the University of Wroclaw. They are used daily, many hours a day. Via multimedia students fulfill their informational, educational, social and communicational aims. In everyday life’s the network environment suppresses contact with such classical media. Due to the fact that Internet applications and communicators accelerate and simplify processes of communication and give the feeling of security.
Keywords: academic youth; electronic media; mediated communication; multimedia